Outcomes of Intradetrusor Onabotulinum Toxin A Therapy in Overactive Bladder Refractory to Sacral Neuromodulation - Trinh, Hamilton (Int Neurourol J, 2019)
PURPOSE: Intradetrusor onabotulinum toxin A (BTXA) and sacral neuromodulation (SNM) are effective third-line therapies for overactive bladder (OAB). We aimed to measure the outcomes of BTXA for treatment of OAB refractory to initial SNM and identify patient characteristics associated with these outcomes. METHODS: This retrospective cohort study included patients who failed to respond to initial SNM treatment for OAB and subsequently received BTXA at a single provider’s clinic between January 2013 and December 2016. Treatment successes were defined as patients willing to continue BTXA or who found symptom relief whereas treatment failures discontinued BTXA due to adverse effects or lack of symptom relief. Symptoms and patient-reported outcomes on validated questionnaires were compared before the initial BTXA trial to 2 months after the last BTXA treatment. The SNM failure BTXA groups were also compared to BTXA SNM naïve groups. RESULTS: Of 18 patients who received BTXA after failed SNM treatment, 7 (39%) achieved treatment success. Successfully treated patients demonstrated decreased urinary frequency from a median 11 voids/day pre-BTXA to 8 voids/day with BTXA (P=0.042). Patients whose treatment failed reported increased complaints of a weak urinary stream (P=0.03) and higher frequency of straining to urinate (P=0.016) than the successful treatment group pre-BTXA. Compared to BTXA patients without prior SNM, the odds of failing BTXA after initial SNM were 3.6 times higher (P=0.016). CONCLUSIONS: BTXA appears effective for OAB refractory to SNM, although the success rate is lower compared to BTXA patients without SNM exposure.